Exploring the Ameliorative Potential of Barleria cristata in Cognitive Dysfunction Rat Model: Investigating Behavioral, Biochemical and Cellular Changes - Chaitanya, Koppala Rakesh Viswa Sai; Korimelli, Sridevi; Gaddam, Supriya Reddy; Kavya, Manuri; Chandupatla, Ramya; Anusha, Venna Rajeswari Surya (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Cognitive impairment is a pervasive and perplexing concern that transcends the boundaries of various neuropsychiatric disorders like schizophrenia and Alzheimer’s. As research continues to unravel the intricacies of Barleria cristata's bioactive compounds, it offers promising prospects for the new therapeutic agents in the realm of natural medicine. Materials and Methods: In present study the ameliorative effect of methanolic leaf extract of Barleria cristata in ketamine induced cognitive dysfunction in rats. Locomotor activity (forced swim test), step down latency and transfer latency were determined for behavioral assessment followed by biochemical estimation of malondialdehyde, reduced glutathione and catalase activity Results: Barleria cristata methanolic extract treatment significantly mitigated cognitive impairment in ketamine induced rats with improvement in short and long term memory. Furthermore, it significantly reduced the lipid peroxidation and improved the levels of reduced glutathione and catalase in rats. On histopathological examination Barleria cristata methanolic extract revealed dose-dependent substantial neuroprotection, by maintaining normal neurons with less neurodegenerative changes. Conclusion: Barleria cristata methanolic extract effectively mitigates cognitive impairment, oxidative stress and neurodegeneration in ketamine-induced rats, demonstrating significant neuroprotective properties.
Keywords: Barleria cristata; Ketamine; Schizophrenia; Step down latency